Caliban and Sycorax or about minority becoming in Our America - Scherbosky, Federica; Visaguirre, Leonardo (Las Torres de Lucca. International Journal of Political Philosophy, 2026)
From a viewpoint based on Our-American political philosophy and critical epistemology, we inquire about Caliban´s potentials and biases as a metaphor to approach political and emancipatory processes in Latin America. We retrieve Fernández Retamar’s proposal to consider the “Calibanesque gaze” as a place of differentiated and emancipatory utterance founded on “cursing”. We provide an account of the conceptual characters that unfold in this philosophical theater as well as of the slave’s journey as he curses in oppressor’s language, revealing the interweaving of race and class. We highlight the epistemological bias of the Calibanesque perspective on women, especially that of Sycorax, his mother murdered by Prospero. As a counterpoint to Caliban's becoming, we propose a becoming-woman that presupposes the intersectionality of race, class, gender, and territory. We do so through the critical contributions of Silvia Federici and Rita Segato, in order to renew the dialectical perspective of Prospero-Caliban and denounce the invisibility and systematic violence against women, perceived as territories of dispute and revenge.
Keywords: Caliban; Sycorax; emancipation; Our-American; intersectionality